Experimental evaluation of the deadtime phenomenon for GM detector: deadtime dependence on operating voltages - AKYÜREK, TAYFUN (NATURE RESEARCH, 2020)
A detailed analysis of Geiger Mueller counter deadtime dependence on operating voltage is presented in the manuscript using four pairs of radiation sources. Based on two-source method, detector deadtime is calculated for a wide range of operating voltages which revealed a peculiar relationship between the operating voltage and the detector deadtime. In the low voltage range, a distinct drop in deadtime was observed where deadtime reached a value as low as a few microseconds (22 mu s for Tl-204, 26 mu s for Cs-137, 9 mu s for Na-22). This sharp drop in the deadtime is possibly due to reduced recombination with increasing voltage. After the lowest point, the deadtime generally increased rapidly to reach a maximum (292 mu s for Tl-204, 277 mu s for Cs-137, 258 mu s for Na-22). This rapid increase in the deadtime is mainly due to the on-set of charge multiplication. After the maximum deadtime values, there was an exponential decrease in the deadtime reaching an asymptotic low where the manufacturer recommended voltage for operation falls. This pattern of deadtime voltage dependence was repeated for all sources tested with the exception of Mn-54. Low count rates leading to a negative deadtime suggested poor statistical nature of the data collected for Mn-54 and the data while being presented here is not used for any inference.